Męczeństwo siedmiu braci machabejskich i ich matki wobec chrześcijańskiej tradycji hagiograficznej - Rusnak, Radosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article focuses upon the description of the massacre of seven Maccabean brothers and their mother, from the seventh chapter of the Second Book of the Maccabees, as one of the most important representational patterns for the chronologically later Christian hagiographic literature, and also outlines theological foundations, developed by the Fathers of the Church, for the inclusion of the heroes of the Jewish uprising from the second century B.C. in the category of martyrdom characteristic of Christianity. In the part devoted to the Old Polish reception of this theme, special attention is devoted to a separate literary rendition of the story, which is the only one of its kind, in "A Pathetic Story of one Mother" by Samuel Dowgird of Pogowie. A detailed analysis focuses on both placing this adaptation within the entire translation work of the Lithuanian author and the idea of its interpretation. The paper is complemented by a critical edition of Dowgird’s work.
The Martyrdom of Seven Maccabean Brothers and their Mother in Christian Hagiographic Tradition
Keywords: Stary Testament; Druga Księga Machabejska; Machabeusze; męczeństwo; hagiografia; Piotr Skarga; Samuel Dowgird z Pogowia; edycja krytyczna; Old Testament; the Second Book of the Maccabees; Maccabees; martyrdom; hagiography; Piotr Skarga; Samuel Dowgird of Pogowie; critical edition